乡村教育发展的根本问题 =The Fundamental Role of Teachers in Rural Education in China /范先佐. - 范, 先佐.
Rural education,being an important part of basic education in China,guarantees the basic human rights and development rights of 40 million rural students and a most effective way to prevent the intergenerational transmission of poverty.Rural education influences the opportunity of bottom class’ flowing upward and also the realization of education modernization in China.Based on the survey of rural schools in 4provinces including Hubei,Jiangxi,Shanxi,Yunnan,analyzing the issues in the development of rural education,this paper thinks that,the weakness of realizing education modernization in China lies in rural areas,with rural teachers playing the most fundamental part in the development of rural education.And the key to developing rural education is to raise rural teachers’ economic payment.